GAMBARAN STATUS GIZI DAN ASUPAN ZAT GIZI PADA IBU HAMIL DI KOTA SEMARANG - Astuti, Rini (Universitas Diponegoro, 2019)
BackgroundPregnant women in Indonesia not only experience deficiencies of macro nutrients, namely carbohydrates, proteins and fats, but also experience micro deficiencies, namely vitamins and minerals. Until now there is no definitive data on the intake of macro and micro nutrients in pregnant women in Indonesia, especially in Semarang. Therefore this study aims to describe nutritional status and nutrient intake in pregnant women Semarang.MethodsThestudy was conducted in the city of Semarang in 2018, using a cross sectional design, with a total sample of 44 pregnant women. Anthropometric data were obtained by measuring the Mid Upper Arm circumference. The intake data was obtained by conducting interviews using a semi-quantitative food frequency questionnaire (SQ-FFQ) form.ResultsIn this study there were 12 (27.3%) pregnant women under the age of 25 years. there are still many nutritional status of pregnant women who are included in the less category which is equal to 38.6%. protein intake, vit B6, and omega 3 fatty acids most of the samples are in the less category. While most saturated fat intake is included in more categories,ConclusionMany nutritional status of pregnant women are included in the less category. In addition, most nutrients needed during pregnancy are still largely lacking.Keywords: pregnancy, nutrition, nutritional status, diet